Partitioning of Fungal Endophyte Assemblages in Root-Parasitic Plant Cynomorium songaricum and Its Host Nitraria tangutorum - Cui, Jin-Long; Vijayakumar, Vinod; Zhang, Gang (Frontiers in Microbiology, 2018)
Endophytic fungi are an integral part and even seen as host organs of plant, influencing physiology, ecology and development of host plants. However, little is known about micro-ecosystems and functional interactions of endophytic fungi in root-parasitic interactions of Cynomorium songaricum and its host Nitraria tangutorum. Here, distribution and dynamics of endophytic fungi were objectively investigated in their associations with C. songaricum and N. tangutorum based on mycobiome studies using high-throughput sequencing. Results suggest that endophytic fungi may be exchanged between C. songaricum and its host N. tangutorum probably through haustorium, connection of xylem and phloem in the vascular system. The similarity of endophytic fungal composition between C. songaricum and parasitized N. tangutorum was 3.88% which was significantly higher than the fungal similarity of 0.10% observed between C. songaricum and non-parasitized N. tangutorum. The similarities of fungal community in parasitized N. tangutorum was much closer to C. songaricum than to the non-parasitized N. tangutorum. The composition of endophytic fungi in these associations increased in progressive developmental stages of C. songaricum from sprouting to above ground emergence, and decreased subsequently probably due to host recognition and response by fungi. However, the shared fungal OTUs increased among interactions of C. songaricum with parasitized and non-parasitized N. tangutorum. Studies of bioactivity on culturable endophytic fungi showed that isolates such as Fusarium spp. possess the ability to promote seed germination of C. songaricum. Our study reports for the first time the special ecological system of endophytic fungi in C. songaricum and its host N. tangutorum. Overall, we hypothesize that a deeper understanding of the sharing, movement and role of endophytic fungi between root-parasitic plant and its host may lead to finding alternative approaches to help increase the output of ethno-pharmacologically important medicinal plants.